Manejo químico de espécies de trapoeraba com aplicação isolada e em mistura de diferentes herbicidas - Martins, Dagoberto [UNESP]; Santana, Diogo Carneiro [UNESP]; de Souza, Guilherme Sasso Ferreira [UNESP]; Bagatta, Murilo Villas Boas [UNESP] (My University, 2012)
This paper evaluated the effect of different herbicides applied isolated and mixed on two species of dayflower (Commelina benghalensis and Commelina villosa). Both species were grown under pot conditions with a capacity of 14 L. Three stems with 10 cm were planted per pot. The herbicides application was made using a stationary spray system, to provide a spray volume of 200 L ha -1, with spray tip XR 110.02VS, when the plants were with dimensions of 25-35 cm for C. benghalensis and 30-35 cm for C. villosa. The mixture saflufenacil more effective control of C. benghalensis were saflufenacil + glyphosate (48 + 720 g ha -1) and, saflufenacil + (glyphosate + imazethapyr) with and without the addition of ammonium sulfate (24 + 623 g ha -1). The combination of carfentrazone + glyphosate (20 + 720 g ha -1) were also effective in the C. benghalensis control. The saflufenacil mixture allowed plant control of C. villosa, where saflufenacil + glyphosate (24 + 720 g ha -1) with the addition of ammonium sulfate, showed a good visually control of this species. The application of 2,4-D (720 g ha -1) and 2,4-D + glyphosate (720 + 720 g ha -1) provided the best visual controls of C. benghalensis e C. villosa. All chemical treatment regardless of Commelina species reduced the dry mass of dayflower.
Chemical management of dayflower species with herbicides applied alono mixture
Keywords: Commelina benghalensis; Commelina villosa; Weed